Model Of Integrating The Values Of Qs. Al-Hujurat Verse 11 Into The Strategies Of Islamic Education Teachers For Character Building In Elementary School Students - Farid, Farid; Kosim, Abdul; Nur, Tajuddin (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to analyze the strategies of Islamic Religious Education (IRE) teachers in integrating the values of QS. Al-Hujurat verse 11 in character building of elementary school students. The focus of the study is on how IRE teachers instill Qur'anic moral values such as respect for others, self-control, and prohibition of slander as part of the character education process in the school environment. This study departs from a research gap that shows that previous studies on Al-Qur'an-based character education have been predominantly conceptual and have not specifically examined the integration of the values of QS. Al-Hujurat verse 11 in the learning strategies of PAI teachers in the context of elementary schools. The research method used is a qualitative approach with a descriptive research type. Data were collected through observation, in-depth interviews, and documentation of Islamic Education learning activities. The results showed that PAI teachers applied various learning strategies, including exemplary behavior, habituation, advice, and a contextual approach through the study of Qur'anic verses. The integration of the values of QS. Al-Hujurat verse 11 proved to play a significant role in shaping attitudes of mutual respect, empathy, and social responsibility in students. The new contribution of this study lies in the formulation of an integrative model of PAI learning strategies based on QS. Al-Hujurat verse 11 that is contextual and applicable, thus complementing previous studies that emphasized normative aspects without empirical mapping of teacher strategies. In conclusion, the implementation of Qur'anic values through PAI teacher learning strategies can be an effective model for strengthening character education in elementary schools in a sustainable manner that is relevant to the social challenges faced by students.